HISTOPATHOLOGY OF THE TELENCEPHALON AND DIENCEPHALON OF T1LAPIA NILOTICA EXPOSED TO SUBLETHAL DOSE OF MALATHION S-[1,2-DI-(ETHOXYCARBONYL ETHYL) DIMETHYL PHOSPHOROTHIOLOTHIONATE] - EDNA A AMPARADO (BIOTROPIA, 1992)
A  35-day  exposure  of  Tilapia  nilotica  embryos  to  sublethal  doses  of  3.0  ppm  and  0.3  ppm malathion,  S-[l,2-di-(ethoxycarbonyl  ethyl)  dimethyl  phosphorothiolothionate],  commercial  grade,  EC  57, produces cellular and ultrastructure changes in the brain. A number of nuclear centers of the treated animals are markedly larger than those of the control. Aberrant features observed in day-45 embryos are the neoplastic masses and increased vascularization. Ultrastructure defects include the presence of nuclear blebs, cytoplasmic vacuolations and increased lysosomal bodies.